Evaluasi Pelaksanaan Cetak Sawah Di Provinsi Kalimantan Barat - Valeriana Darwis (Jurnal Penelitian Pertanian Terapan, 2019)
Food, especially rice, is a basic human ingredient whose needs increase following thepopulation growth. On the other hand the availability of rice has decreased following theland conversion rate. To overcome land conversion and to increase national rice production,the government made policy of paddy expansion / printing. In 2016 this activity isimplemented in 27 provinces and has been printed new fields of 129,096 ha. One of theprovinces that get the rice field printing program is West Kalimantan Province. From theresults of the evaluation, the location of the new paddy fields is in accordance with theobjectives of the program, namely: rice fields have been formed, farmers who work aroundthe location of land and water sources for cultivation is also available. From the paddy fieldexperience of 2016, the improvements required for next year's paddy fields include: (i) preferably planning (SI & D) in advance a year is made than the implementation and (ii) additionalpaddy rice costs, as the cost of expensive tool mobilization and social costs and (iii) a bindingrule in the form of sanctions for the farmer who converted the new fields. As for improvingthe required crop index: water management; subsidizing inputs (seeds, fertilizers, lime, farming tools and cultivation training.